2014
DOI: 10.1002/lary.24548
|View full text |Cite
|
Sign up to set email alerts
|

Preliminary data on two voice therapy interventions in the treatment of presbyphonia

Abstract: Findings provide new evidence regarding the efficacy of voice therapy exercises in the treatment of age-related dysphonia and suggest PhoRTE therapy as another treatment method for improved voice-related quality of life and reduced perceived vocal effort in this population.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

2
48
0
20

Year Published

2014
2014
2021
2021

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 125 publications
(70 citation statements)
references
References 34 publications
2
48
0
20
Order By: Relevance
“…In relation to the self-evaluation, it was noticed a significant improvement in V-RQOL, scores 19,23 , in the Dysphonia Risk Screening Protocol 21 , a decrease in Vocal Handicap Index scores, self-reported positive effect of the therapeutic program on voice 17,19 , significant reduction in perception of the phonation effort 19 , a decrease in inadequate habits and vocal symptoms 9. In physical therapy, it is observed that the literature of the period from 2004 to 2014 showed only 11 research on respiratory therapy in healthy elderly subjects: three using the Threshold machine, two with incentive spirometry, with a manual therapy, with the use of breathing exercises associated with the trunk and upper limb movement in soil and aquatic environment and four involving physical activity.…”
Section: Discussionmentioning
confidence: 97%
See 2 more Smart Citations
“…In relation to the self-evaluation, it was noticed a significant improvement in V-RQOL, scores 19,23 , in the Dysphonia Risk Screening Protocol 21 , a decrease in Vocal Handicap Index scores, self-reported positive effect of the therapeutic program on voice 17,19 , significant reduction in perception of the phonation effort 19 , a decrease in inadequate habits and vocal symptoms 9. In physical therapy, it is observed that the literature of the period from 2004 to 2014 showed only 11 research on respiratory therapy in healthy elderly subjects: three using the Threshold machine, two with incentive spirometry, with a manual therapy, with the use of breathing exercises associated with the trunk and upper limb movement in soil and aquatic environment and four involving physical activity.…”
Section: Discussionmentioning
confidence: 97%
“…It is supposed that the vocal phonotherapy work and respiratory physiotherapy might optimize the treatment and provide more benefits to patients, especially if they can occur in an associated way 2 . The literature that was consulted during the period from 2004 to 2014 showed only 11 research on vocal phonotherapy in healthy elderly people: one through vocal orientation 9 ; three with specific vocal exercises, such as, TMF support of vowels and musical scales with vowels and words 18 , sounded blowing 5 and the Finnish method of resonance tubes 22 ; two carried out a review of medical records of elderly who underwent voice therapy for presbyphonia, regardless of the kind of intervention 23,24 ; five of them applied therapeutic programs: the Lee Silverman 20 method, the Vocal Cognitive Program 21 , the program of vocal function exercises of Stemple 16,17 , and the comparison between the vocal function method and the PhoRTE 19 . The results of speech therapy with elderly people showed an improvement in voice quality in relation to the aspects of roughness 17,22 , breathiness 20,22 , asthenia 20,22 , instability 22 , tension 22 , loudness 20,21 and the general level of the vocal disorder 15,18,20,21,22,24 ; a decrease in effort phonation 18 , an improvement in resonance 18 and articulation clarity 21 .…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Contempla ejercicios de fortalecimiento para el control respiratorio y fonatorio mediante la educación vocal y postural aumentando la coordinación neuromuscular de todo el conjunto. Esto lleva a la mejora en la comunicación oral mediante la disminución del esfuerzo al hablar y el ajuste de la calidad vocal en función de las necesidades de la edad [12]. Los ejercicios vocales han sido propuestos para favorecer el cierre glótico, aumentar la presión subglótica y la intensidad de la voz, estabilizar la calidad vocal y la frecuencia fundamental, además de proveer una mejoría global del habla.…”
Section: Causasunclassified
“…Los protocolos deben abarcar ejercicios fonatorios de alta intensidad para sobrecargar el sistema respiratorio y laríngeo y mejorar la intensidad vocal y reducir el esfuerzo vocal. Siempre se debe recomendar la terapia de voz inicialmente cuando se haya determinado que la presbilaringe es la causa del cambio de voz [12,13]. Los fallos en la terapia de voz se deben principalmente a que se requiere de múltiples visitas al rehabilitador que muchas veces no se pueden cumplir asociado la mayoría de veces a pacientes con atrofia de cuerdas vocales severa o que cursan con enfermedad sistémica, especialmente pulmonar [13].…”
Section: Causasunclassified